Answer:
3
Explanation:
5x-3y=23
4x-4y=20
---------------I'm going to try to set this up for elimination. I notice the bottom equation contains terms that are divisible by 4 so I'm going to divide both sides by 4 on that last equation only...
5x-3y=23
x- y= 5
Now I'm going to multiply the bottom equation by -3 so the y terms will be opposite. When you add opposites you do get 0. That is the whole point of elimination.
5x-3y=23
-3x+3y=-15
------------------ adding
2x+0=8
2x =8
x =4
So using that second equation x-y=5 I will find y given that x=4.
4-y=5
-y =1
y=-1
So the solution to the system is (4,-1)
You are asked to find x+y
So x+y=4+(-1)=3